Open and closed industry clusters: the social structure of innovation - Ferreira, Manuel Portugal (2011)
In this paper we discuss knowledge and innovation in clusters and the benefits of clustering from a knowledge-based perspective. Knowledgebased resources and innovations are important sources of competitive advantage for firms. Aware of the importance of continuously seeking new knowledge firms increasingly seek knowledge-rich locations such as specific industry clusters across the world. These are locations characterized by the concentration of firms operating in related and supporting activities, a specialized work force and a specialized institutional environment that nurtures the industry. However, it is not likely that these clusters are always locations from which the firms will be able to draw the intended knowledge benefits. The social structure of the relationships between individuals and firms determines the extent to which knowledge will be created, will flow between co-located firms and bounds the knowledge benefits the firms may capture. We finish with a discussion of the need of further examination of the network dynamics involved in an industry cluster to obtain a clearer identification of the actual positive externalities that may accrue to co-locating firms.